Kate Landry has a plan [large type] - Millet, Rebekah (Millet, Rebekah. Beignets for two, 2025)
"Kate Landry's life has become as messy as the powdered sugar on her famous beignets. Juggling the responsibilities of running her café, raising her teenage niece, and the emotional baggage from her breakup, Kate finds her world turned upside down when her first-ever crush, Micah Guidry, returns to town as the hunky local librarian. As Kate struggles to implement her plans to expand her café amid the New Orleans Mardi Gras madness and the meddling of her ex-fiancé, Micah becomes the unwitting hero of her misadventures, stirring up feelings she thought she'd long buried. How can falling in love in the Big Easy be this hard?"--Page 4 of cover.